1989
DOI: 10.1002/pen.760291803
|View full text |Cite
|
Sign up to set email alerts
|

Control of transesterification in polyester blends

Abstract: Polyester blends may undergo transesterification during processing, resulting in molecular rearrangements, transient properties, and eventually, degradation. To suppress transesterifcation, the use of organophosphites has been suggested in the patent and technical literature. The effectiveness of organophosphites, however, is variable and sometimes inconsistent. Our recent studies suggest a clue to the inconsistent behavior and provide a simple way to enhance the effectiveness of these stabilizers. Using solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 11 publications
0
24
0
1
Order By: Relevance
“…It is reported that phosphoric acid interact with the polycondensation catalysts thereby modifying the catalyst [30][31][32][33]. Since the same catalyst catalyses the thermal degradation addition of phosphoric acid mitigates degradation reactions.…”
Section: Effect Of Thermal Stabilizer On the Thermal Degradationmentioning
confidence: 99%
“…It is reported that phosphoric acid interact with the polycondensation catalysts thereby modifying the catalyst [30][31][32][33]. Since the same catalyst catalyses the thermal degradation addition of phosphoric acid mitigates degradation reactions.…”
Section: Effect Of Thermal Stabilizer On the Thermal Degradationmentioning
confidence: 99%
“…Melt-phase blending of PET with PEN causes transesterification reactions to occur between the two polymers, which result in the formation of block copolymers that become more random as the reactions proceed. [7][8][9][10][11][12] Studies conducted by Porter and Wang 13 have shown that both PET and PEN are immiscible; however, transesterification reactions increased the blend miscibility through the formation of copolymers. Good mixing was necessary before the blends became transparent.…”
mentioning
confidence: 99%
“…This holds particularly for the PETP and PBT blends. The ester interchange reaction does not need to be stopped in PAr -PCHT blends due to its complete miscibility [104][105][106][107].…”
Section: Polyarylates and Copolyarylate -Carbonate Blendsmentioning
confidence: 99%